Diskurs - interdisziplinär: Zugänge, Gegenstände, Perspektiven - Kämper, Heidrun; Warnke, Ingo H. (Diskursmuster, 2015)
"What happens when philosophers and sociologists, historians, literary scholars, and linguists try to engage in discourse? The essays in this volume examine this question and describe the structure of discourses as instances of meaning-production based on a common basic understanding of "discourse" from a theoretical, methodological, and empirical perspective"--